Penerapan Terapi Hiperbarik Oksigen Terhadap Penyembuhan Luka Pada Pasien Ulkus Kaki Diabetik: Studi Literatur - Khairunisa, Aida; Herdianto, Pulung; Mifta, Elja; Syamsuddin, Asniah (Journal Keperawatan, 2024)
Background: Diabetic foot ulcers are advanced complications experienced by people with diabetes mellitus that have a negative impact and must be treated immediately. One method that can be done to overcome the incidence of diabetic foot ulcers is hyperbaric oxygen therapy. This therapy is known to facilitate wound healing by improving wound tissue perfusion, increasing fibroblast replication and collagen production and increasing phagocytic ability. Purpose: The purpose of this study was to determine the application of hyperbaric oxygen therapy to wound healing in diabetic foot ulcer patients. Methods: The method used in this writing is literature review, with secondary data obtained from previous research with empirical studies of the last 10 years, data sources are accessed through the google scholar database, by taking journals that are relevant to the research topic. Results: This study shows that the results that have been carried out on the administration of hyperbaric oxygen therapy to diabetic foot ulcers, show the ability to heal wounds in a fast time and more effective results. Conclusion: Based on the results of literature review research by collecting several journals, it is concluded that the management of hyperbaric oxygen therapy in diabetic foot ulcer patients is more effective, cost-effective, and increases the prevalence of wound healing.